2022
DOI: 10.1007/s10389-021-01689-6
|View full text |Cite
|
Sign up to set email alerts
|

Violence against physicians and nurses: a systematic literature review

Abstract: Background Violence against physicians and nurses is a global public health problem. This study explored violence against physicians and nurses using a systematic literature review. Methods Pubmed and Scopus were searched using search words ‘violence’ OR ‘aggression’ ‘against’ ‘physicians’ AND ‘nurses’. Articles published between 2010 and 2020 in the English language, excluding review/systemic review articles, were included in the study. We used the Prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…Participants stated that safety in a public healthcare facility is a challenge. Violence against healthcare workers, including learner nurses, is not new and has been a pandemic [ 48 , 49 ]. Although there is an interconnection of literature describing violence in the workplace, not many studies documented the safety and violent incidents against learner nurses during CL.…”
Section: Discussionmentioning
confidence: 99%
“…Participants stated that safety in a public healthcare facility is a challenge. Violence against healthcare workers, including learner nurses, is not new and has been a pandemic [ 48 , 49 ]. Although there is an interconnection of literature describing violence in the workplace, not many studies documented the safety and violent incidents against learner nurses during CL.…”
Section: Discussionmentioning
confidence: 99%
“…Turgut et al (2021) reported that the most common reason for violent behavior in Turkey was the patients' or their relatives' dissatisfaction with health services (38%). Recently, Chakraborty et al (2022) reviewed 22 studies that showed significant violent incidents. Verbal abuses were the highest among all settings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…12 Lack of communication plays an important role in problems related to the current trend of doctor-patient relationship with increasing litigations and violence against doctors. 13 As there is no standardized teaching and assessment of communication skills for postgraduate medical students in Indian medical schools, this study aimed to assess the effectiveness of a training program on the communication skills of postgraduate students and to assess the perceptions of postgraduate students towards training program.…”
Section: Introductionmentioning
confidence: 99%